Impact of COVID-19 Pandemic from Farm to Fork: Hard-won Lessons - Anwar, Md Parvez (Fundamental and Applied Agriculture, 2020)
As evident from the past, although pandemic is a health issue it could lead to food security and economic crises. Since agriculture accounts for more than 3.3% of global gross domestic product and 60% of the population depends on agriculture for their livelihoods, COVID-19 pandemic impact on agriculture may result in acute hunger and malnutrition, and the deepest global reces- sion in recent history. Agriculture is experiencing a huge challenge in dealing with both supply and demand shocks. Globally, there is sufficient food to feed the people but the challenge is to make food available to everyone due to logistic bottlenecks and high price. The hard-won lessons from this pan- demic is that ‘feeding the world is always a challenging task’ and therefore we should search for a more resilient, sustainable and regenerative food production and supply system to cope with such a crisis. Prompt response and immediate acceleration are needed to support the recovery process and minimize deterioration. Agri-food sector must be reoriented so that it can function more effectively in the post COVID-19 era.